A Case Study of Teaching Single Variable Calculus Traditionally vs. Virtually: A Semester Bifurcated. Issue 7 (9th August 2022) - Collins, Christopher A.; Galbreath, David R.
Abstract : The pedagogical discussion between the merits of traditional learning versus online learning provides much discussion from both camps. Following the Coronavirus of 2019 pandemic in the spring of 2020, undergraduate students enrolled in the freshman Single Variable Calculus course at the United States Military Academy at West Point were forced to switch from traditional, in-person classes to learning virtually at the half-way mark of the semester. This provides an interesting case study, showing the dichotomy of a semester bifurcated; half of a semester in a traditional classroom and the other half in an online one. Comparing the transition and techniques of analogous approaches to a virtual learning experience, the framework of dynamic and static teaching approaches is explored through analytic reflection.